Acute Effects of Dry Needling on Myofascial Trigger Points in the Triceps Surae of Ballet Dancers: A Pilot Randomized Controlled Trial - Jennifer A Janowski; Deanna M L Phelan-Smith; Maria N Kroat Brady; Kelsey L Michels; Alexandra H Timm; Nicole M Boucher; Kedron D Casteen; David Village; Mark D Sleeper (International Journal of Sports Physical Therapy)
# Background